Anisakis spp. as indicators of latitudinal movements of short‐finned pilot whales, Globicephala macrorhynchus , in the Northeast Atlantic - Claudia Pons‐Bordas; Rachel V. Pool; Sofía Ten; José A. Armenteros‐Santos; Ana Balseiro; Manena Fayos; F. Javier Aznar (Marine Mammal Science, 2025)
In the Northeast Atlantic, it is unclear whether short‐finned pilot whales, Globicephala macrorhynchus (SFPWs), are transient or resident above 40°N. We used Anisakis spp. to identify the latitudes recently visited by a SFPW pod stranded in NW Spain (43°N) in 2020. Analysis of cox2 gene in 30 nematodes from 6 SFPWs revealed the presence of A. simplex sensu stricto (s.s.) (93.3%) and A. pegreffii (6.7%). Morphological analysis of 972 nematodes corroborated species molecular identification and relative proportions; in males ( n = 66), the estimated proportions of A. simplex s.s. and A. pegreffii were 86.4% and 13.6%, respectively. These percentages resembled those reported in fish/cetaceans above 40°N, and L4 larvae or adults of A. typica (a tropical‐temperate species found in SFPWs up to 38°N–39°N) were not detected. Population structure of A. simplex s.s. + A. pegreffii in SFPWs suggested a continuous recruitment of nematodes starting at least 3 weeks before stranding. We interpret that either the SFPW pod was within the range of the species (perhaps as a recent northern shift) or represented a vagrant group that visited waters off Northwest Spain for a protracted period. Future analysis on nematode assemblages could shed light on movements and climate‐driven shifts in cetacean distribution.